Quality status and quality aspects in the Icelandic construction industry - Sandra Dagbjartsdóttir 1986- (2012)
A common discussion is that the construction industry lacks efficiency, quality is poor, budgets are unreliable and prices are excessive. Better management would result in increased efficiency with reduced quality failures while saving tremendous amount of money. This research aims at identifying and documenting the current status of the construction quality in Iceland. This involves identifying the main problems and point out where the scope lies for improving and by what means it is possible to do so. To begin with, a literature review was performed in order to analyze the status of quality in construction with regards to quality problems and quality aspects. After having analyzed the data, a questionnaire was designed and sent to construction professionals, both with engineering firms and contractors firms. Finally interviews were conducted with quality professionals in organizations whom staff had participated in the questionnaire. The research strongly suggests that quality is a problem for the construction industry in Iceland. The research revealed that there is a scope for improving quality and it is possible. This conclusion is both supported with literature research and the research results. The research revealed that quality professionals saw clear improvements in organizational operations after having implemented a quality management system. Furthermore the general employee had a very positive view towards applying and using the system on his work. However the research suggests that there is a gap in the use and implementation of quality management systems and that knowledge needs to be improved. The training and teaching methods on using and implementing quality management systems is in general inadequate, especially amongst the contractors. 47% of participants with the engineering firms were satisfied with the amount of training received while only 30% of participants with the contractor firms were satisfied with the training received on implementing the system. The research revealed that the ...